2007
DOI: 10.1109/tnb.2007.909008
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal Quantum Dot-Conjugated Anti-Myeloperoxidase Antibody as the Detector of Activated Neutrophils

Abstract: Fluorescent nanocrystal quantum dots (QDs) have been applied to a wide range of biological studies by taking advantage of their fluorescence properties. Here we show that QDs conjugated with antibody against neutrophil peroxidase, myeloperoxidase (MPO). We designed a novel method to conjugate QDs to antibody without losing any antibody function including their antigen recognizing and Fc-receptor binding activities. When we applied anti-MPO antibody (Ab) with conventional organic probes in the case of immunosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…5b). In addition, MPO translocation on neutrophils was observed at a concentration of 10 Ϫ8 M FMLP, that is consistent with the result that human neutrophils show chemoattraction on FMLP at 10 Ϫ8 M (18). However, CAWS stimulation induces no MPO translocation (Fig.…”
Section: Neutrophils Of Anca-associated Glomerulonephritis Model Micesupporting
confidence: 90%
See 1 more Smart Citation
“…5b). In addition, MPO translocation on neutrophils was observed at a concentration of 10 Ϫ8 M FMLP, that is consistent with the result that human neutrophils show chemoattraction on FMLP at 10 Ϫ8 M (18). However, CAWS stimulation induces no MPO translocation (Fig.…”
Section: Neutrophils Of Anca-associated Glomerulonephritis Model Micesupporting
confidence: 90%
“…The antibody captured on QD measured with the Bradford reagent (BioRad Laboratories, Hercules, Calif., U.S.A.) with the standard curve of bovine serum albumin indicated that each ANCA-QD had approximately 8.5 Abs per QD nanocrystal (data not shown, see ref. 18). The function of ANCA-QD was checked by fluorescent Western blotting and histochemical analysis (39).…”
Section: Methodsmentioning
confidence: 99%
“…These observations are consistent with our results that neutrophils also produce IL-23 and mediate the Th 17 -medicated immune response. The higher ANCA titer is probably established by repeated MPO leakage on the membrane surface due to repeated or chronic fungal infection [28]. Th 17 and IL-17-mediated immune responses are required for the appropriate immunity for the prevention of fungal infection, but unfortunately in some cases it facilitates the resting Th 17 -mediated immune response while activating the neutrophils inappropriately via excessive proinflammatory cytokine induction, thus finally resulting in an autoimmune disorder.…”
Section: Discussionmentioning
confidence: 99%
“…4a). To test whether this separation process activates the neutrophils, we confirmed the surface expression of MPOs, whose expression is observed only on the membrane surface of activated neutrophils [28]. The surface expression of MPO is not observed in purified peritoneal neutrophils (Fig.…”
Section: Activated Neutrophils Have the Ability To Produce Il-17a In mentioning
confidence: 97%
“…Cadmium-based QDs are of special interest because they have unique photonic properties and photonic stability [6], and they are currently being used in fluorescent biodetection systems [79] including bio-imaging performed in vitro [10,11] and in vivo [1215]. Our group investigated the efficacy of the QDs modified with various chemicals, antibodies and ligands as specific biological probes [1619]. …”
Section: Introductionmentioning
confidence: 99%